2019
DOI: 10.3390/min9120747
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Modified Montmorillonite and Its Application to Rare Earth Adsorption

Abstract: Montmorillonite, the major clay mineral in the tailings of weathered crust elution-deposited rare earth ores, was modified as an excellent adsorbent to enrich rare earth ions from solutions. It was demonstrated that 5% H 2 SO 4 could be used as a modifier to effectively enhance the adsorption capacity of montmorillonite after modifying for 3 h with a liquid:solid ratio of 40:1 at 90 • C. A superior modified montmorillonite over montmorillonite on adsorption performance was analyzed by the XRD, FT-IR, SEM, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Wang et al [ 37 ] studied the adsorption behaviour of Nd(III) ions using o-carboxymethyl chitosan entrapped by silica. They reported that the adsorption capacity of o-carboxymethyl chitosan was significantly improved by support on SiO 2 and reached 53.04 mg/g at 328 K. The montmorillonite was prepared, modified and applied to adsorb La(III) and Y(III) by Liu et al [ 38 ]. The maximum adsorption capacities for the modified montmorillonite were 0.178 mmol/g for La(III) and 0.182 mmol/g for Y(III).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [ 37 ] studied the adsorption behaviour of Nd(III) ions using o-carboxymethyl chitosan entrapped by silica. They reported that the adsorption capacity of o-carboxymethyl chitosan was significantly improved by support on SiO 2 and reached 53.04 mg/g at 328 K. The montmorillonite was prepared, modified and applied to adsorb La(III) and Y(III) by Liu et al [ 38 ]. The maximum adsorption capacities for the modified montmorillonite were 0.178 mmol/g for La(III) and 0.182 mmol/g for Y(III).…”
Section: Resultsmentioning
confidence: 99%
“…The Montmorillonite was modified by hexadecyl trimethyl ammonium bromide (HDTMA) and sodium diethyl dithiocarbamate (DDTC). The maximum of sorption capacity for La(III) was 0.178 mmol/g and was higher than for Nitrolite [33].…”
Section: Comparison With the Other Natural Sorbentsmentioning
confidence: 77%
“…With the change of the environ-ment of the solution system, especially at higher temperatures, RE 2 (CO 3 ) 3 was able to be hydrolyzed into RECO 3 (OH), and CO 2 was released again, which also indicates that the pores of the mixed phase may be caused by the release of CO 2 [20,21]. In this process, the porous surface of tRECO 3 (OH) has a strong adsorption effect on F − in the solution, and the adsorbed F − replaces OH − on the RECO 3 (OH) surface by ion exchange [22][23][24][25][26][27][28][29][30]. Finally, tREFCO 3 is generated on the RECO 3 (OH) surface.…”
Section: Intensitymentioning
confidence: 99%